Influences of aging on tenderness and color of beef steaks - R.R. Timm; K.A. Hachmeister; L.M. Sammel; A.E. Rasor; John A. Unruh; Sally L. Stroda (Kansas Agricultural Experiment Station Research Reports, 2001)
Aging loin strip, bottom, and eye of round steaks for 21 days decreased Warner- Bratzler Shear (WBS) values (increased tenderness). For the top round, aged semimembranosus muscle steaks tended to have lower WBS values (more tender) than nonaged steaks, while aged adductor steaks were similar to non-aged steaks. Furthermore, instrumental L* color values were higher (lighter) for aged strip and eye of round steaks than non-aged steaks, and instrumental a* color values were higher (redder) for aged bottom round, eye of round, and top round (semimembranosus) steaks than nonaged steaks. Aging steaks is effective for improving tenderness and color of strip, bottom, top (semimembranosus) and eye of round steaks.
Keywords: Cattlemen& #x27; s Day; 2001; Kansas Agricultural Experiment Station contribution; no. 01-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 873; Beef; Aging; Color; Tenderness